An exploratory study on how meaningful the KFC brand is in the context of food waste management - Badrinath, Sanam (The IIE, 2022)
The purpose of this research project was to explore and understand how meaningful the KFC brand is in the context of food waste management. The research followed a qualitative methodology by making use of in-depth interviews to explore the three core themes of meaningful brands, consumer behaviour and social media. Data collected in this study was analysed using a thematic approach and indicated that although KFC has engaged in sustainable initiatives, the awareness from a consumer point of view is minimal and social media is not being utilised enough currently by KFC to effectively communicate their sustainable efforts. This study concludes that although KFC might be actively involved in sustainable programmes and initiatives, they are not being perceived to be as meaningful of a brand as they could be. There needs to be more visibility from KFC to enhance the sustainable aspect of their brand perception. It is recommended that KFC puts more effort into creating marketing strategies that their audiences are receptive to, so that they can effectively communicate their current sustainable initiatives and promote new ones.
Keywords: Meaningful brands; Consumer behavior; Fast food; Restaurants